An association study revealed substantial effects of dominance, epistasis and substance dependence co‐morbidity on alcohol dependence symptom count. (5th May 2016) - Chen, Gang; Zhang, Futao; Xue, Wenda; Wu, Ruyan; Xu, Haiming; Wang, Kesheng; Zhu, Jun
Abstract: Alcohol dependence is a complex disease involving polygenes, environment and their interactions. Inadequate consideration of these interactions may have hampered the progress on genome‐wide association studies of alcohol dependence. By using the dataset of the Study of Addiction: Genetics and Environment with 3838 subjects, we conducted a genome‐wide association studies of alcohol dependence symptom count (ADSC) with a full genetic model considering additive, dominance, epistasis and their interactions with ethnicity, as well as conditions of co‐morbid substance dependence. Twenty quantitative trait single nucleotide polymorphisms (QTSs) showed highly significant associations with ADSC, including four previously reported genes ( ADH1C, PKNOX2, CPE and KCNB2 ) and the reported intergenic rs1363605, supporting the overall validity of the analysis. Two QTSs within or near ADH1C showed very strong association in a dominance inheritance mode and increased the phenotype value of ADSC when the effect of co‐morbid opiate or marijuana dependence was controlled. Highly significant association was also identified in variants within four novel genes ( RGS6, FMN1, NRM and BPTF ), two non‐coding RNA and two epistasis loci. QTS rs7616413, located near PTPRG encoding a protein tyrosine phosphatase receptor, interacted with rs10090742 within ANGPT1 encoding a protein tyrosine phosphatase in an additive × additive or dominance × additive manner. The detected QTSs contributed to about 20 percent of total heritability, in which dominance and epistasis effects accounted for over 50 percent. These results demonstrated that perturbations arising from gene–gene interaction and conditions of co‐morbidity substantially influence the genetic architecture of complex trait. Abstract : We conducted a genome‐wide association studies of alcohol dependence symptom count with a full genetic model considering additive, dominance, epistasis and their interactions with ethnicity, as well as conditions of co‐morbid substance dependence. Twenty quantitative trait SNPs (QTSs) were identified, including four previously reported genes such as ADH1C, four novel genes, two non‐coding RNAs and two epistasis loci. The detected QTSs contributed to about 20 percent of total heritability, in which dominance and epistasis effects accounted for over 50 percent.